Syndrome of Inappropriate Antidiuretic Hormone secretion due to hydroxyurea - Hakan Ozer; Yasin Ozturk; Ismail Baloglu; Kultigin Turkmen (Archives of Clinical Nephrology - Peertechz Publications, 2022)
Hyponatremia is the most common electrolyte disorder in clinical practice: Syndrome of Inappropriate Antidiuretic Hormone Secretion (SIADH) is the most common cause of hyponatremia, especially in euvolemic patients. Drugs are among the most common causes of SIADH. While our patient was using hydroxyurea due to polycythemia vera, he was diagnosed with SIADH due to hydroxyurea treatment after investigation due to resistant hyponatremia. The improvement of hyponatremia after hydroxyurea is discontinued and the development of hyponatremia after the drug is re-started supports the development of drug-induced hyponatremia. Careful follow-up is required in terms of hyponatremia in patients using hydroxyurea.